A variational approach for accurate prediction of stress and displacement fields and thermo-elastic constants in general symmetric laminates containing ply cracking and delamination under general triaxial loading - Hajikazemi, M.; Ahmadi, H.; McCartney, L.N.; Van Paepegem, W. (International journal of solids and structures, 2022)
Delamination induced by ply cracking is an important damage mechanism that results in stress redistribution and degrades both the in-plane and out-of-plane laminate properties. In this work, a novel variational model is first developed that accurately predicts stress and displacement fields in arbitrary symmetric laminates, containing uniformly spaced ply cracks in a single orientation with delaminations on the interfaces between the plies at the tips of ply cracks, subject to general triaxial loading and thermal residual stresses. The model is then used to predict the dependence of the in-plane and out-of-plane laminate thermo-elastic properties on ply crack density and delamination length. The results are extensively compared with those obtained from refined finite element methods and available experiments, showing excellent accordance.